Forward-looking reaction to bank regulation - Risto Herrala (European Central Bank (ECB), 2014)
This paper presents evidence that banks react to regulation in a forward-looking manner. A case study documents a reaction to Basel II as early as 2000, in other words about seven years prior to the implementation of the regulation in 2007. Based on the initial information released on Basel II, banks loosened their credit policies towards households. The changes were substantial, improving household credit availability by 20-50%. A new approach to estimate borrowing constraints from loan samples is also presented.
Keywords: D14; E32; E51; G21; 330; bank regulation; borrowing constraints; credit policy